Strut Linker Geometry Improving Mechanical Behaviorof Coronary Stent - Rachmat Sriwijaya; Dita Ayu Mayasari; Siti Sunarintyas (Universitas Gadjah Mada, 2020)
Stent is one of the common solution that is offered to the patient with atherosclerosis. An ideal stent should have good mechanical and biological properties. This research aims to analyze how importance strut linker geometry affect mechanical behavior of stent especially on recoil percentage, foreshortening percentage and fatigue safety factor prediction using finite element analysis. The result showed that strut linker geometry would specify the mechanical behavior